2019
DOI: 10.4236/ojcm.2019.93016
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Static Flexural Properties of a Pultruded Glass Fiber/Unsaturated Polyester Square Pipe

Abstract: This paper explores quasi-static flexural properties and fracture behavior of a pultruded glass fiber/unsaturated polyester square pipe for automotive structural applications. Three-point flexural testing is performed in an Instron Universal Testing Machine with steel jigs supporting the top and bottom surfaces of the pipe. Acoustic emission (AE) measurements are recorded during flexural testing to evaluate initial fracture in the pipe structure. After final fracture, five cross-sections of the pipe are cut at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…They reported the relationship between AE measurements and bending test. AE measurements were able to find out the initial fracture stress [15].…”
Section: Introductionmentioning
confidence: 99%
“…They reported the relationship between AE measurements and bending test. AE measurements were able to find out the initial fracture stress [15].…”
Section: Introductionmentioning
confidence: 99%
“…Jing Rong studied the change law of parameters related to resin flow during the pultrusion process of glass fiber/polypropylene composite yarn. [ 23 ] They found that parameters such as pre tension and forming temperature have a significant impact on the performance of pultrusion tubes. Hui alleviates the defect of wrinkle and fracture of pipe fittings by reducing the axial compressive stress at the upper end and the tensile stress at the lower end during the forming process of thin‐walled pipes.…”
Section: Introductionmentioning
confidence: 99%